(3GdJPcQI GdWGgQjIs - (3WGgQ Hf UGdM (B((3Ch eMeO UGdM(B) (3GHf CMeO Hf ehgH, GdSeYhfj GdLRGFQj, Ke GdOeTbj,J (B1338 (3g` s
(3ChdgG (B:s
(3ebGdI eWHhYI ddTjN YHO GdbGOQ GdeZQHi YVh GdeLeY GdYdei HOeTb fTQJ ai LQjOI GdebJHS GdCQHYGA (B24 (3ef QHjY GdChd SfI (B1341(3g` ai hUa GdLRGA GdehLhOI efgG HOGQ GdcJH GdYQHjI HOeTb s
(3BNQgG (B:s
(3hYR GdSGOI GdCYdGe , bVGI GdESdGe , GdeYOjf dSO GdPQjYI hTO GQcGf GdTQjYI , GdPHf ZeQhfi HHQgge , hLejY ef MVQ ai gPG GdecGf GdeHGQc , hSGge ai gPg GdCLRGA hTGQc s
(3hgj eLehYI cHjQI ef JSLjd eWGdYGJg Ydi GdcJH GdBJjI hQDjJg dgG(B: (3JfRjg GdTQjYI GdeQahYI Yf GdCNHGQ GdTfjYI GdehVhYI dGHf YQGbLRA cHjQ ef JGQjN GdHNGQis
(3hGdeUHGM ai GdfMh dfGUQ Hf YHO GdSjO GdeWQRis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B35s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B169 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs